Humoral and cellular immunity to measles and rubella virus antigens in healthy subjects - M. A. Smerdova (Sankt-Peterburg : NIIÈM imeni Pastera, 2019)
An issue of eradicating measles and rubella virus-induced infections currently remains unresolved, despite existing effective methods for specific prophylaxis and WHO’s commitment to a mass vaccination policy. While improving epidemic situation, analysis of new challenges, such as measles incidence in adults, especially in adults vaccinated in childhood, is of particular interest. The aim of the study was to analyze serum measles and rubella virus-specific IgG antibodies in young healthy people and estimate antigen-specific cellular immune response in seronegative subjects. There were examined 100 healthy adults aged 18–30 years old. Level of serum specific IgG was measured by ELISA (Vector-Best, Russia). Antigen-specific cellular immune response was assessed by magnitude of surface CD107a expression on CD8hi T cells challenged by measles and rubella virus-derived antigens. It was found that average level of antibodies against rubella virus comprised 175.5 IU/ml, 49% of which recovered after rubella, 46% were vaccinated, whereas 5% subjects contained no virus-specific antibodies. In addition, mean level of anti-measles virus antibodies was below protective magnitude, among which 1% subjects recovered after measles, 31% displayed post-vaccination immunity, 55% subjects were seronegative, and 13% had equivocal levels of specific antibodies. Thus, 68% subjects were unprotected against measles virus based on the level of serum virus-specific antibodies. Moreover, 40 out of 68 subjects were vaccinated against measles in childhood. Additional screening adult subjects for intensity of measles and rubella virus-specific cellular immunity demonstrated that 57.37% of them contained peripheral blood CD8 T cells against measles virus and 59.01% — against rubella virus. Further analysis allowed to identify 4 subgroups displaying: 1) high level of virus-specific antibodies and T cells; 2) neither antibodies nor specific T-cells reaching as low as 20% of baseline group; 3) high antibody level combined with low amount of specific T cells; and 4) low antibody level combined with high level of specific T cells. thus, it may be assumed that cellular and humoral immune arms are maintained independently and being active for a long term after vaccination. Preserving a specific T-cell immunity seems to provide protection against infection, thereby accounting for the lack of measles manifestation in all seronegative subjects.